Effect of Pre-treatments for Enhancing the Germination of Adansonia digitata L. and Cochlospermum religiosum L. - Gahane, R. N.; Kogje, K. K. (Indian Forester, 2013)
The present study deals with breaking the seed dormancy by various physical and chemical agents and establishment of seedlings of Adansonia digitata and Cochlospermum religiosum. In A. digitata, pre treatment with concentrated sulphuric acid for 12 hrs exhibited 68% germination which was further enhanced up to 90.67% by post treatment soaking in 0.1M glucose solution. C. religiosum exhibited 32% germination with pre treatment of sulphuric acid for 25 min and with post treatment soaking in 0.1M glucose solution showed 54.67% germination. Seedling survival was also found to be more in the combination treatment of sulphuric acid and 0.1M glucose solution (A. digitata- 81.33% and C. religiosum- 53.33%) than pure sulphuric acid treatment.